Human CD6 Down-Modulation following T-Cell Activation Compromises Lymphocyte Survival and Proliferative Responses - Carrasco, Esther; Escoda-Ferran, Cristina; Climent, Núria; Miró-Julià, Cristina; Simões, Inês T.; Martínez-Florensa, Mario; Sarukhan, Adelaida; Carreras, Esther; Lozano, Francisco (Frontiers in Immunology, 2017)
Available evidence indicates that the CD6 lymphocyte surface receptor is involved in T-cell developmental and activation processes, by facilitating cell-to-cell adhesive contacts with antigen presenting cells and likely modulating T-cell receptor (TCR) signaling. Here, we show that in vitro activation of human T-cells under different TCR-ligation conditions leads to surface down-regulation of CD6 expression. This phenomenon was i) concomitant to increased levels of soluble CD6 in culture supernatants, ii) partially reverted by protease inhibitors, iii) no associated down-regulated in CD6 mRNA levels, and iv) reversible by stimulus removal. CD6 down-modulation inversely correlated with up-regulation of CD25 in both FoxP3- (Tact) and FoxP3+ (Treg) cell subsets. Furthermore, ex vivo analysis of peripheral CD4+ and CD8+ T-cells with activated (CD25+) or effector memory (TEM, CD45RA-CCR7-) phenotype present lower CD6 levels than their naïve or central memory (TCM, CD45RA-CCR7+) counterparts. CD6lo/- T-cells resulting from in vitro T-cell activation show higher apoptosis and lower proliferation levels than CD6hi T-cells, supporting the relevance of CD6 in the induction of proper T-cell proliferative responses and resistance to apoptosis. Accordingly, CD6 transfectants also showed higher viability when exposed to TCR-independent apoptosis-inducing conditions in comparison with untransfected cells. Taken together, these results provide insight into the origin of soluble CD6 and the previously reported circulating CD6-negative T-cell subset in humans, as well as into the functional consequences of CD6 down-modulation on ongoing T-cell responses, which includes sensitization to apoptotic events and attenuation of T-cell proliferative responses.